Genetic diversity and population structure of Eritrean pepper (Capsicum species) as revealed by SSR markers - Saleh, B.K.; Kasili, R.W.; Mamati, Edward George; Yao, N.; Villiers, S.M. de; Araia, W.; Nyende, A.B. (Sophia Publishing Group, Inc., 2016)
Pepper (Capsicum spp.) is one of the most important vegetable crops and the most widely used spice worldwide including Eritrea. Diversity studies are an essential step for crop breeding and improvement. Therefore, the objectives of the study were to determine the diversity and population structure of local Eritrean pepper collected from farmers and research institutions and to evaluate the relatedness of the Eritrean pepper with accessions obtained from five other countries. A total of 407 individual pepper plants from 150 seed samples were evaluated using 28 SSR markers. The results showed that varieties maintained in situ by farmers were heterogeneous. Diversity parameters indicated extensive genetic variation among the Eritrea genotypes. The 28 markers revealed a total of 352 alleles with an average of 13 alleles per marker. Mean Polymorphic Information Content was 0.62 and, mean Observed Heterozygosity was 0.41. The analysis of molecular variance showed only 10% variation was among populations, 30% among individuals within populations and 60% within individuals. This can be explained by the high mean number of effective migrants (2.25) that ranged from 1.01 to 10.45 among populations indicating movement of germplasm among farmers in different geographic and agro-ecological regions. A factor analysis, neighbour joining clustering and the model based clustering (Structure) classified the 407 individuals into 3 groups. However, in the model based clustering; increasing the number of populations to 4 (K=4 ) caused all non-Eritrean genotypes to fall in a separate cluster suggesting availability of potentially rich diversity within the Eritrean populations justified by the large number of private alleles observed.